Piloting reusable plastic crates in the tomato value chain in Tanzania - Mvungi, Henry; Ernest, Zablon; Mwambi, Mercy; Bruno, Theresia; Kok, Melanie; Dijkxhoorn, Youri (CGIAR System Organization, 2025)
This study shows that reusable plastic crates outperform traditional wooden crates in reducing postharvest losses and maintaining tomato quality throughout the supply chain in northern Tanzania. Traditional wooden crates have a weight loss of 1.9% from farm to retailer, and the plastic crates only have a loss of 1%. Reusable plastic crates minimize compression damage and overloading, leading to lower weight and quality losses compared to traditional wooden crates. Additionally, tomatoes transported in plastic crates achieved higher market value, as better quality resulted in improved prices.